2019
DOI: 10.2495/str190291
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Rock Units From the Pompeii Archaeological Site, Italy

Abstract: The definition of compatible conservation interventions on the archaeological built asset requires a comprehensive knowledge of physical, chemical and mechanical properties of the ancient masonry structures and their components. However, information on the mechanical properties of units, mortars and masonry assemblages are still lacking especially with reference to one of the most popular UNESCO World Heritage Sites in Italy, the Pompeii archaeological site. Thus, the paper focuses on the mechanical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…UNI, 2010 for Italian conditions or CEN, 2016 for a broader European context), possibly reduced according to service and load duration classes (CEN, 2004). Recent studies found an average specific weight of about 2000 kg/m 3 for lava specimens (Autiero, De Martino, Di Ludovico, & Prota, 2019b), about 1200 kg/m 3 for mortars (Autiero, De Martino, Di Ludovico, & Prota, 2019a;Miriello et al, 2010). These values may be extended also to the calculation of floor slabs weight.…”
Section: Definition Of An Analytical Modelmentioning
confidence: 71%
“…UNI, 2010 for Italian conditions or CEN, 2016 for a broader European context), possibly reduced according to service and load duration classes (CEN, 2004). Recent studies found an average specific weight of about 2000 kg/m 3 for lava specimens (Autiero, De Martino, Di Ludovico, & Prota, 2019b), about 1200 kg/m 3 for mortars (Autiero, De Martino, Di Ludovico, & Prota, 2019a;Miriello et al, 2010). These values may be extended also to the calculation of floor slabs weight.…”
Section: Definition Of An Analytical Modelmentioning
confidence: 71%
“…"calcare del Sarno", "lava" and "cruma"). Over the course of the archaeological excavation work started in May 2018 at the Regio V, it was possible to collect original units of such rock types from the newly-emerged ruins [5]. A brief description of such rock types is summarized in Table 1.…”
Section: Original Rock Unitsmentioning
confidence: 99%
“…Original rock units from the ruins emerged in the excavation works in Regio V started in May 2018 and pozzolanic lime-based mortars compliant with the traditional typologies were selected to built the panels. Thus, a preliminary investigation of the mechanical properties of the single building materials was carried out including the execution of both NDTs and DTs [4,5]. Therefore, three panels (1.20m x 1.20m x 0.45m) were built and sonic pulse velocity tests were performed in order to provide a useful tool for a comparison with the same tests performed on original structures at the site.…”
Section: Introductionmentioning
confidence: 99%